2004
DOI: 10.1002/rra.779
|View full text |Cite
|
Sign up to set email alerts
|

BIO‐SAFE: assessing the impact of physical reconstruction on protected and endangered species

Abstract: Assessing actual and potential biodiversity of river-floodplain ecosystems on the basis of policy and legislation concerning endangered and protected species is necessary for consistency between different policy goals. It is thus a prerequisite to sustainable and integrated river management. This paper presents BIO-SAFE, a transnational model that quantifies the relevance of species and ecotopes, characteristic of the main channels and floodplains of the rivers Rhine and Meuse, on the basis of international tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Therefore, with a high sedimentation rate, landscaping measures like lowering of the floodplain will have to be repeated more often. Thirdly, the potential biodiversity values improve for the green and yellow scenario and decrease for the orange scenario, which is in line with expectations about effects of various types of landscaping measures (De Nooij et al, 2004). Finally, potential toxicological effects of cadmium contamination in the floodplain soil, as computed by SpaCE-S, were revealed for 4-5 out of 10 wildlife species.…”
Section: Biogeomorphological Changessupporting
confidence: 81%
See 3 more Smart Citations
“…Therefore, with a high sedimentation rate, landscaping measures like lowering of the floodplain will have to be repeated more often. Thirdly, the potential biodiversity values improve for the green and yellow scenario and decrease for the orange scenario, which is in line with expectations about effects of various types of landscaping measures (De Nooij et al, 2004). Finally, potential toxicological effects of cadmium contamination in the floodplain soil, as computed by SpaCE-S, were revealed for 4-5 out of 10 wildlife species.…”
Section: Biogeomorphological Changessupporting
confidence: 81%
“…The pollutants, such as heavy metals, are incorporated in the ecological food-chain (Torres and Johnson, 2001). The hydrodynamics and inundation frequency also influence the ecotope distribution (Deil, 2005), while the ecotope distribution in turn determines the potential biodiversity (De Nooij et al, 2004). Altogether, these and other studies revealed the complex biogeomorphological interactions that characterize these floodplain environments.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…General targets for nature development must therefore be set in an early stage of the development of flood protection strategies. This target can be the protection of rare species, the enhancement of biodiversity (De Nooij et al, 2004), restoration of natural river processes (e.g. in the form of cyclic rejuvenation: Duel et al, 2001;Baptist et al, 2004, the optimization of nutrient retention (Hoekstra et al, 2002), or still other objectives.…”
Section: Integrating Flood Risk Management Objectives With Other Polimentioning
confidence: 98%